Does the belt and road initiative reduce the carbon emission intensity of African participating countries? - Dusengemungu, Didier-Robert; Liu, Jinhao; Zhou, Zhifang (Environmental science and pollution research international, 2023)
The ambition of the Belt and Road Initiative (BRI) became an integral part of carbon emission abatement. The BRI impact on African participating countries’ battle against carbon emissions intensity is a contentious subject. Urbanization and industrialization are the main sources of CO 2 emissions in Africa and the driving force in the BRI. Using data on variables from 2010 to 2019 in 54 African countries, applying Difference-in-differences model (DID) and Propensity Score Matching-Difference-in-differences regression (PSM-DID), and robustness tests to investigate if the BRI’s participation tends to reduce the carbon emissions intensity of African participating countries. This study finds that African countries’ participation in the BRI minimizes the intensity of carbon emissions in those countries. Further analysis shows that low carbon development of BRI countries is more significant in countries that joined the BRI than those that did not join it. In addition, our results show that improving economic transformation such as the innovation in technology and industries’ structures can boost the CO 2 emission reduction technologies. These findings suggest that developing BRI collaboration with China will benefit the environment and African BRI participating countries’ ability to achieve sustainable development. Our results further support the BRI’s effect and recommend policy implications and methods for those countries’ CO 2 emission prevention and control actions.